ANTI-INFLAMMATORY PROPERTIES AND IMMUNOADJUVANT ACTIVITIY OF SAMANEA SAMAN EXTRACT - Barbosa, Antony de Paula (Emirates Journal of Food and Agriculture, 2014)
Samanea saman is a Leguminosae widely distributed in tropical regions, especially in Brazil. In folk medicine is used to treat skin infections, gastric inflammation and parasitic infestations, but there is no report in literature on its phytochemical. In order to confirm the utilization of this species in the traditional medicine, the anti-inflammatory activity of the chloroform extract and the immunoadjuvant activity of the butanolic extract were investigated. The chloroform extract exhibited a moderate control of the initial phase of inflammation, provoking an inhibition of edema formation similar to the reference compound dexamethasone. The butanolic extract showed a relevant adjuvant potential in comparison with the commercial extract of Quillaja saponaria, a commonly used adjuvant for experimental vaccine formulations.